ID-based service-oriented communications for unified access to IoT. (May 2016) - Mongay Batalla, Jordi; Gajewski, Mariusz; Latoszek, Waldemar; Krawiec, Piotr; Mavromoustakis, Constandinos X.; Mastorakis, George
Abstract: The dynamic development of technologies for smart devices and the increasing availability of sensors and actuators facilitate significantly the implementation of the Internet of Things (IoT) solutions. The massive use of the IoT depends on the simplification of the set-up and management of the systems, which makes the service creation and composition easier. This paper discusses a prototyped implementation of IDSECOM (ID-based SErvice-oriented COMmunications for unified access in IoT): an innovative hierarchical network infrastructure for connecting IoT objects and services in an easy-to-manage and flexible way. This solution is appropriate when the location of the nodes is closely related to the structure of the environment as it occurs in intelligent buildings/enterprises.